Generating equations using meta-analyses to predict iodine value of pork carcass back, belly, and jowl fat - Paul, Chad B.; Bergstrom, J. R.; Tokach, Michael D.; Dritz, Steven S.; Burnett, Derris D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Gonzalez, John M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
Meta-analyses used data from existing literature to generate equations to predict finishing pig back, belly, and jowl fat iodine value (IV) followed by a prospective study to validate these equations. The final database included 24, 21, and 29 papers for back, belly, and jowl fat IV, respectively. For experiments that changed dietary fatty acid composition, initial diets (INT) were defined as those fed before the change in diet composition and final diets (FIN) were those fed after. The predictor variables tested were divided into 5 groups: (1) diet fat composition (dietary % C16:1, C18:1, C18:2, C18:3, essential fatty acid [EFA], UFA, and iodine value product) for both INT and FIN diets; (2) duration of feeding the INT and FIN diets; (3) ME or NE of the INT and FIN diet; (4) performance criteria (initial BW, final BW, ADG, ADFI, and G:F); and (5) carcass criteria (HCW and backfat thickness). PROC MIXED in SAS (SAS Institute, Inc., Cary, NC) was used to develop regression equations. Evaluation of models with significant terms was then conducted based on the Bayesian Information Criterion (BIC). The optimum equations to predict back, belly, and jowl fat IV were: backfat IV =84.83 + (6.87*INT EFA) - (3.90*FIN EFA) - (0.12*INT d) - (1.30*FIN d) - (0.11*INT EFA*FIN d) + (0.048*FIN EFA*INT d) + (0.12*FIN EFA*FIN d) - (0.0132*FIN NE) + (0.0011*FIN NE*FIN d) - (6.604*BF); belly fat IV = 106.16 + (6.21*INT EFA) - (1.50*FIN d) - (0.11*INT EFA*FIN d) - (0.0265*INT NE) + (0.00152*INT NE*FIN d) - (0.0816*HCW) - (6.35*BF); and jowl fat IV = 85.50 + (1.08*INT EFA) + (0.87*FIN EFA) - (0.014*INT d) - (0.050*FIN d) + (0.038*INT EFA*INT d) + (0.054*FIN EFA*FIN d) - (0.0146*INT NE) + (0.0322*INT BW) - (0.993*ADFI) - (7.366*BF), where INT EFA = initial period dietary essential fatty acids, %; FIN EFA = final period dietary essential fatty acids, %; INT d = initial period days; FIN d=final period days; INT NE = initial period dietary net energy, kcal/lb; FIN NE = final period dietary net energy, kcal/lb; BF = backfat depth, in.; ADFI = average daily feed intake, lb; INT BW = BW at the beginning of the experiment, lb. Dietary treatments from the validation experiment (see “Influence of Dietary Fat Source and Feeding Duration on Pig Growth Performance, Carcass Composition, and Fat Quality,” p. 210) consisted of a corn-soybean meal control diet with no added fat or a 3 × 3 factorial arrangement with main effects of fat source (4% tallow, 4% soybean oil, or a blend of 2% tallow and 2% soybean oil) and feeding duration (d 0 to 42, 42 to 84, or 0 to 84). The back, belly, and jowl fat IV equations tended to overestimate IV when actual IV values were less than approximately 65 g/100 g and underestimate belly fat IV when actual IV values were greater than approximately 74 g/100 g or when the blend or soybean oil diets were fed from d 42 to 84. Overall, with the exceptions noted, the regression equations were an accurate tool for predicting carcass fat quality based on dietary and pig performance factors.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Iodine value; Meta-analysis; Pork quality